Development of Problem-Based Learning (PBL) Ethnoscience Based Teaching Materials Food and Beverage Additives Material to Improve Students’ Science Literacy - Ana Fransiska Utami; Agung Tri Prasetya; Woro Sumarni (Unnes Science Education Journal, 2025)
This study aims to develop Problem-Based Learning (PBL) teaching materials integrated with an ethnoscience approach on the topic of food and beverage additives to enhance students’ scientific literacy. The research was motivated by the low level of scientific literacy among Indonesian students, as indicated by the 2022 PISA results, which suggest that science learning remains largely theoretical and insufficiently connected to local cultural contexts. The ethnoscience approach integrates scientific concepts with indigenous cultural knowledge, while the PBL model promotes active learning, critical thinking, and problem-solving skills. This study employed a Research and Development (R&D) method using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The research subjects were eighth-grade students at SMP Islam Sunan Giri Salatiga. Research instruments included expert validation sheets for materials and media, student response questionnaires, and scientific literacy tests. Data were analyzed using descriptive quantitative and qualitative techniques to determine the feasibility, practicality, and effectiveness of the developed teaching materials. The results indicate that the PBL–ethnoscience-based teaching materials are highly valid, with average validation scores of 89.38% from material experts and 87.68% from media experts. Student responses were categorized as very good, with scores of 80.61% on a small scale and 81.45% on a large scale. The N-gain analysis showed improvements in scientific literacy at high (41.94%), moderate (38.71%), and low (9.68%) levels. These findings demonstrate that PBL–ethnoscience-based teaching materials effectively improve junior high school students’ scientific literacy and can serve as a reference for culturally integrated science learning.